Optimasi Yoghurt Sari Kedelai (Glycine Max L) Tinggi Serat dan Protein: Optimasi Yoghurt Sari Kedelai (Glycine Max L) Tinggi Serat dan Protein - Dyah Kartika Wening; Purbowati; Nafisah (Amerta Nutrition, 2022)
Background: Yogurt is a fermented milk product using microbial bacteria. Yogurt is generally made from cow's milk, but with innovation, it can be made from vegetable ingredients. Vegetable-based yogurt has the potential to be developed because it has functional properties and high nutritional value. Yogurt is made from nuts, which has high fiber nutritional value, free of lactose and casein, one of which is soybeans. Objectives: To produce a formulation of soy yoghurt (Glycine max L) with high fiber and protein nutritional value that is acceptable to the public. Methods: The study design was laboratory observational food production using a completely randomized design. This research used 1 experimental unit and 4 treatments were carried out. The research was conducted in three stages, the first was to optimize the best yogurt formula by dividing Soygurt Formula 1 (FS1 was soybean extract using a 5% commercial starter; FS2 was a proportion of 2.5%; FS3 was soybean extract using a 5% LB/ST starter; FS4 with a proportion of 2.5%.The second stage was a hedonic test to get the best product that could be accepted by the community.The third stage was a test for fiber content and protein content of the selected product. Results: Based on the hedonic test, FS1 and FS3 were equally favored with the average results of FS 1 texture 3.12, taste 3.36, color 3.44, aroma 3.76; and FS3 texture 3.16, taste 3.28, color 3.52, aroma 3.52. FS1 is the most preferred yogurt and contains 6,39 g of fiber with 21,48 g of protein and 6,74 g of fat in every 100 grams of yogurt. Conclusion: Based on the results of the analysis, soygurt is a high-fiber drink because it has more fiber content than the SNI, which is 4,473 g for each serving. In addition, soygurt has a higher protein content than SNI, which is 15,036 g per serving.